Developing digital learning media of Artsteps virtual exhibition on food chain material - Putri Nur Fitriana; Kurniana Bektiningsih; W. Wikanso (Research and Development in Education (RaDEn), 2024)
The low student learned outcomes on the topic of food chains, as well as the less varied instructional media used by teachers, was the background of this researched. This researched aimed to developed, assess the feasibility, and tested the effectiveness of the Artsteps Virtual Exhibition learned media in enhancing learned outcomes on food chain material for fifth-grade students at one of elementary school in Semarang City. This typed of researched researched and development (R&D) utilizing the Borg and Gall development model, which consisted of 10 stages. However, the researcher only reached stage 9. Subject mattered experts and media experts conducted the product validity tested. The results of this researched included the development process of artsteps learned media on the topic of food chains; the validity of Artsteps learned media, which assessed as highly valid from students' responses to Artsteps learned media fell into the category of excellent; and the SPSS result indicating a significant difference in outcomes before and after the treatment. Therefore, Artsteps learned media could improved students' learning outcomes on food chain material.